Recalibrating Labour Law: A Critical Institutional Analysis of the Labour Relations Act in South Africa - Manga Mokofe, William (Eastasouth Institute, 2025)
This paper critically analyses the Labour Relations Act (LRA) by examining its efficiency and institutional dynamics, focusing on its influence on workplace relations, collective bargaining, and dispute resolution. The LRA seeks to strike a balance between fostering economic productivity and protecting workers’ rights, yet its implementation is frequently influenced by broader institutional factors such as legal precedents, evolving policies, and socio-economic realities. The study assesses whether the LRA successfully promotes labour market efficiency or if institutional limitations hinder its effectiveness in achieving its goals. By integrating comparative perspectives and case law applications, the paper identifies key challenges in the operation of the Act and explores the tensions between legal frameworks and practical outcomes. Additionally, it proposes policy recommendations aimed at creating a more adaptable and equitable labour system, addressing the complexities that impact the law’s capacity to respond to changing market conditions. This analysis ultimately calls for a rethinking of the LRA’s approach to better align with contemporary labour market needs while ensuring fairness for all stakeholders.